2011
DOI: 10.1167/iovs.11-7867
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Preservation of Cone Photoreceptors and Restoration of Cone Function by Gene Therapy in the Guanylate Cyclase-1 Knockout (GC1KO) Mouse

Abstract: The authors demonstrate for the first time that long-term therapy (∼1 year) is achievable in a mammalian model of GC1 deficiency. These data provide additional justification for the development of an AAV-based gene therapy vector for the clinical treatment of Leber congenital amaurosis-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 48 publications
7
82
1
Order By: Relevance
“…This concurs with prior detailed expression studies in the zebrafish, using in situ hybridization and immunohistochemistry by Rätscho et al 44 These results confirmed the location of the mRNA of photoreceptorspecific Gucy2ds by in situ hybridization techniques for all Gucy2ds between 3 and 4 days post fertilization suggesting that their controlled expression coincides with the onset of visual function. Studies in mice with the GC1 null allele 45 reveal that, although GC1 is also expressed in rods, it has a crucial role in cone function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This concurs with prior detailed expression studies in the zebrafish, using in situ hybridization and immunohistochemistry by Rätscho et al 44 These results confirmed the location of the mRNA of photoreceptorspecific Gucy2ds by in situ hybridization techniques for all Gucy2ds between 3 and 4 days post fertilization suggesting that their controlled expression coincides with the onset of visual function. Studies in mice with the GC1 null allele 45 reveal that, although GC1 is also expressed in rods, it has a crucial role in cone function.…”
Section: Discussionmentioning
confidence: 99%
“…47 Therapy results on the GCdko mouse have yet to be published, 49 but talks and posters have indicated that gene replacement was a success, conferring long-term therapy to both rods and cones (Boye et al 45 , personal communication), demonstrating this model as a true phenotypic mammalian model of LCA1. 45 Using the optomotor response assay, untreated GC1KO mouse eyes perform poorly with a visual acuity of 0.16 ± 0.04 cycles per degree, whereas isogenic GC1+/+ control eyes responded significantly better, showing an average acuity of 0.42 ± 0.05 cycles per degree. Gene replacement-treated eyes displayed an average acuity of 0.39±0.08 cycles per degree, a level essentially identical to control +/+ eyes and significantly better than untreated GC1KO eyes (Po0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of age-matched wild-type (WT) mice served as controls. At sacrifice, tissue was prepared according to published methods (Boye et al, 2011). Eyes designated for cryosectioning were processed and immunostained as described (Haire et al, 2006;Pang et al, 2010).…”
Section: Tissue Preparation Immunohistochemistry and Microscopymentioning
confidence: 99%
“…Sections were counterstained with 4', 6'-diaminio-2-phenylindole (DAPI) for 5 min at room temperature. Retinal sections were imaged as previously described (Boye et al, 2011).…”
Section: Tissue Preparation Immunohistochemistry and Microscopymentioning
confidence: 99%
“…In contrast, foveal, parafoveal, perifoveal, and peripheral cones of nonhuman primates were all effectively transduced following subretinal delivery of AAV5-hGRK1-GFP (10 10 vg delivered) . As in rodent retinas (Khani et al 2007;Tan et al 2009;Boye et al 2010Boye et al , 2011Pawlyk et al 2010;Sun et al 2010), hGRK1 has exclusive activity in cones and rods of nonhuman primates . Taken together, these results support the use of a subretinally delivered AAV5 vector containing the hGRK1 promoter for delivering GUCY2D in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%